Kinematic Analysis During Straight Line Free Swimming in Horses: Part 2 - Hindlimbs - Santosuosso, Emma; Leguillette, Renaud; Vinardell, Tatiana; Filho, Silvio; Massie, Shannon; McCrae, Persephone; Johnson, Sarah; Rolian, Campbell; David, Florent (Frontiers in Veterinary Science, 2022)
Background: Swimming is used for rehabilitation and conditioning purposes in equine sports medicine. We described the swimming kinematics of the equine forelimbs in Part 1. The aim of Part 2 is to assess stifle, tarsus, and fetlock joints kinematics in swimming horses. The objectives were 1-to calculate and compare joint angles during swimming against passive mobilizations (PM), 2- to determine joints angular velocities during a swimming stride cycle. Methods: Eleven elite endurance horses were used to swim in a 100-meter straight pool. Underwater (swimming) and overground PM videos were recorded from the horses’ left side. Joint markers were applied on the lateral hoof wall, lateral metatarsal epicondyle, lateral aspect of the talus, lateral femoral epicondyle, and great trochanter of the femur. As a reference, maximal fetlock, tarsus, and stifle flexion/extension angles were determined during passive mobilization (PM) overground. Differences between angle extrema, angular velocities, and range of motion (ROM) were statistically compared. Results: The tarsus ROM was similar during PM and swimming. The stifle and fetlock ROM were greater during PM, although the stifle flexion was greater during swimming. The stifle and tarsus had the greatest hindlimb angular velocity during the swimming cycle. Greater angular velocities were observed during the retraction phase for all hindlimb joints. Conclusion: A short retraction phase with great angular velocity for the joints of interest characterized the swimming pattern observed. Swimming may be beneficial in horses when an increased ROM of the tarsus and stifle or a reduced fetlock extension is recommended for rehabilitation purposes.